A Study of Dynamic Right-Turn Signal Control Strategy at Mixed Traffic Flow Intersections - Zhizhou Wu; Li Zhao; Jian Sun (Promet - Traffic&Transportation, 2014)
Traffic conflicts among right-turn vehicles (RTVs), non-motorized vehicles (NMVs) and pedestrians were examined for urban signalized intersections with exclusive right-turn lane. This study proposed an approach to dynamically calculate the duration of the prohibited right-turn for vehicles by using a measure called the Degree of Clustered Conflict (DCC). The process of DCC control includes: 1) quantitative calculation of DCC value in the conflict area; 2) establishing the general cost model that combines the delay and conflict indicators; and 3) applying the DCC-control time model to control RTV in real time. Based on these, the paper presented a general approach of detailed dynamic on-line signal control process of RTV. Finally, the RTV control process was programmed based on VISSIM simulation to evaluate the control effectiveness. The results showed that the general cost (weighted summation of delay and conflict) of the RTV control decreases rapidly compared with non-control, fixed control and full control (drop of 58%, 35% and 42% under small flow conditions and 70%, 59% and 17% in the large flow conditions, respectively). The method not only improved the operation efficiency, but also reduced the potential safety risks among traffic participants when vehicles turn right at intersections.